Regional Labour Market Adjustment and the Movements of People: A Review - David C Maré; Wai Kin Choy (New Zealand Government, The Treasury, 2001)
This review paper examines the link between internal migration and regional labour market adjustment. It outlines the motivation and scope of our enquiry, discusses the three key questions that we plan to pursue, reviews relevant international and New Zealand literature, and outlines proposals for future research. The first key question examines whether migration helps regional labour market adjustment. The second question investigates how important migration is as a regional labour market adjustment mechanism. The final question looks at who is moving and whether it matters for regional labour market adjustment.
Keywords: R23; J61; 330; regional labour market; internal migration; regional labour market adjustment